Strategic Financial Determinants of Shareholder Value: Analizing the Moderating Role of Price-to-Book Value in Indonesia Banking - Asdar Asdar; Dimas Angga Negoro (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Stock returns reflect the condition of the company while presenting investor perceptions of these shares. This study aims to analyze the effect of return on assets, return on equity, BOPO, capital adequacy ratio, loan deposit to ratio, net interest margin on stock returns with price to book value as a moderating variable in banking companies in 2014-2018. The data collection technique used purposive sampling with a population of eleven banking companies that publish financial statements and are listed on the Indonesia Stock Exchange from 2014 to 2018. Testing was conducted using EViews 9 software with panel data regression and fixed effect model. The results show that return on assets, return on equity, BOPO, loan to deposit ratio have no significant effect on stock returns, while net interest margin has a negative and significant effect, capital adequacy ratio has a positive and significant effect, and net interest margin moderated by price to book value has a positive and significant effect on stock returns.